2018
DOI: 10.3174/ajnr.a5605
|View full text |Cite
|
Sign up to set email alerts
|

Under Pressure: Comparison of Aspiration Techniques for Endovascular Mechanical Thrombectomy

Abstract: Sixty-milliliter VacLok vacuum pressure syringes and the Dominant Flex suction pump achieved high and constant flows likely sufficient to reverse blood flow during thrombectomy with an 8F sheath or balloon-guide catheter in the ICA and modern distal aspiration catheters in the MCA. The Pump MAX aspiration pump is dedicated for use with distal aspiration catheters and is unlikely to reverse blood flow in the ICA and MCA without balloon protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…The authors suggest that this may be due to an optimised ratio between the size of the vessel and the aspiration catheter that leads to better ingestion of the clot. Whilst this seems plausible and is in line with in vitro studies published by Nikoubashman et al [14,15], this issue is reduced with the use of stent retrievers since they, by design, adapt to the vessel diameter and therefore minimise issues of size. A sub-group analysis of the ASTER trial data comparing the results of patients with M1 clots would help to shed light on whether there is an optimal strategy based on clot location especially given that the majority of patients in this trial had clots that were located in the M1 segment.…”
Section: Predictors Of Success With Aspirationsupporting
confidence: 58%
“…The authors suggest that this may be due to an optimised ratio between the size of the vessel and the aspiration catheter that leads to better ingestion of the clot. Whilst this seems plausible and is in line with in vitro studies published by Nikoubashman et al [14,15], this issue is reduced with the use of stent retrievers since they, by design, adapt to the vessel diameter and therefore minimise issues of size. A sub-group analysis of the ASTER trial data comparing the results of patients with M1 clots would help to shed light on whether there is an optimal strategy based on clot location especially given that the majority of patients in this trial had clots that were located in the M1 segment.…”
Section: Predictors Of Success With Aspirationsupporting
confidence: 58%
“…The 8F sheath resulted in an average reduction of vessel diameter and cross-sectional area of 61% and 37%, respectively, and the sheath did not significantly reduce blood flow (236 Ϯ 25 mL/min, P ϭ . 19). Pump aspiration resulted in a significant flow reduction with a net flow of 225 Ϯ 25 mL/min (P Ͻ .001) (Fig 2).…”
Section: Resultsmentioning
confidence: 99%
“…In an average patient and without application of a balloon-guide catheter, which restricts antegrade flow, the amount of aspirated blood in the ICA should surpass its normal flow of 240 mL/min to achieve reliable flow reversal. 19 There is an ongoing discussion of whether BGCs or large-bore sheaths are needed for effective flow management. Large-bore sheaths allow aspiration of high-flow volumes up to approximately 1000 mL/ min.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have assessed the technical characteristics of various catheters and aspiration techniques in generating optimal suction forces. Nikoubashman et al observed consistently high suction flow rates with both a 60 cc vacuum syringe and the Medela Flex pump, compared with the Penumbra Max aspiration system 9. This result held true for a variety of catheter types, from an 8-French long sheath (Shuttle Select, Cook, Illinois, USA) to a smaller Catalyst six distal access catheter (Stryker, Michigan, USA).…”
Section: Discussionmentioning
confidence: 96%